TREATMENT OF PATIENTS WITH GIANT CELL BONE TUMOR IN NORTHERN BRAZIL, IN 2020 AND 2021 - Fernando Brasil do Couto Filho; Eduardo Sadao Yonamine; Felipe Guimarães Magno; Ana Beatriz Favacho-Silva; Carlos Rafael Alves de Brito; Thiago Raphael Brasil Brito (Acta Ortopédica Brasileira)
Abstract Objective: This study aimed to evaluate the profile of patients diagnosed with giant cell tumors treated at the Ophir Loyola Hospital. Method: An analytical study in the form of a retrospective cohort, conducted through a review of patient medical records and imaging exams of individuals treated at the hospital between January 1, 2020, and December 31, 2021. Result: A total of 19 patients were evaluated, with an average time of 10.5 months between diagnostic suspicion and the first consultation with the Orthopedic Oncology team. Conclusion: Among the patients studied, 73% were presented with advanced-stage disease, requiring aggressive surgical treatment with wide resection and replacement with an endoprosthesis. Level of Evidence II; Retrospective Prognostic Study.